In and out and out again: The travails of Brazil as a security provider in Africa - Seabra, P.; Marcondes, D. (Brazil-Africa relations in the 21st century: From surge to downturn and beyond, 2021)
The story of Brazil as a contemporary security actor in Africa can prove a peculiar one. Marked by quick gains and an equally quick recognition over a short period of time, it has also been followed by an equally quick turnaround which has led, as of 2020, to a visible disengagement on the ground. We explore the main travails in this domain, which have compromised much of the gains previously obtained throughout the continent. The chapter begins with a general balance of the progress achieved between 2003 and 2016, followed by the highlights of the recent downturn. We then analyze a specific sub-area, namely, the inroads carried out at the defence industry level, in order to showcase the promises and contradictions often associated to what the country has offered across the Atlantic. We conclude by presenting some opportunities for a new pickup of Brazilian interest in the middle and long run.